2002
DOI: 10.1291/hypres.25.389
|View full text |Cite
|
Sign up to set email alerts
|

Association of G-33A Polymorphism in the Thrombomodulin Gene with Myocardial Infarction in Koreans.

Abstract: Thrombomodulin (TM), a thrombin receptor expressed on the endothelial surface, is known to play an important role in the anti-thrombogenic system in vivo. In this study, we examined the effects of 3 single-nucleotide polymorphisms (SNPs) in the TM gene (G 33A, C1418T and C1922T) on the development of myocardial infarction (MI) in Koreans. We found that G 33A was a common SNP (the minor allele frequency was 0.09) in Koreans. Eighty-five MI patients who had received coronary angiography were enrolled and were di- Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
4
25
2
Order By: Relevance
“…The G33A polymorphism in thrombomodulin gene reduces promoter activity and was signiWcantly associated with MI (Ireland et al 1997;Park et al 2002), CAD (Li et al 2000) and carotid atherosclerosis (Li et al 2001). Conversely, in another study no association between the G33A polymorphism and CAD/MI was observed (Zhao et al 2005).…”
Section: Genes Associated With Arterial Thrombosismentioning
confidence: 94%
See 1 more Smart Citation
“…The G33A polymorphism in thrombomodulin gene reduces promoter activity and was signiWcantly associated with MI (Ireland et al 1997;Park et al 2002), CAD (Li et al 2000) and carotid atherosclerosis (Li et al 2001). Conversely, in another study no association between the G33A polymorphism and CAD/MI was observed (Zhao et al 2005).…”
Section: Genes Associated With Arterial Thrombosismentioning
confidence: 94%
“…The 1G/ 2G polymorphism in the MMP-1 gene could inXuence risk of CAD (Ye et al 2003) and the MMP-1 2G/2G genotype in combination with stromelysin-1 6A/6A genotype signiWcantly increased the risk factor for carotid artery atherosclerosis (Ghilardi et al 2002). The MMP9 (Gelatinase B) C1562T polymorphism was also associated with CAD risk (Cho et al 2002;Ghilardi et al 2002;Zhang et al 1999). In a large study an association of composite C1562T/R279Q polymorphisms in MMP-9 gene with MI was observed.…”
Section: Genes Associated With Vascular Remodelingmentioning
confidence: 99%
“…Individuals, especially young patients in Taiwan, with the G-33A polymorphism carry a higher risk of acute myocardial infarction (22), and the risk is further increased by smoking (6). Similarly, in Koreans, the G-33A polymorphism of the TM gene may be a genetic risk factor for myocardial infarction, as a result of abnormal promoter activity (23). In the Japanese population, those with a haplotype consisting of A2729C and C1418T of the TM gene have a higher risk of developing deep vein thrombosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the promoter region of the TM gene were more common in patients diagnosed with MI than in matched controls. 146 The −33A allele has been associated with an increased risk of AMI and carotid atherosclerosis, [147][148][149] however, not consistently. 150 In the SMILE, the 25Thr allele was associated with MI, especially in young men and in the presence of additional risk factors (such as smoking and the presence of a metabolic risk factor: obesity, hypertension, or hypercholesterolemia).…”
Section: Protein C Pathwaymentioning
confidence: 99%